Evidence for a Fast Soft X-Ray Wind in M82 from XMM-RGS - Erin Boettcher; Edmund Hodges-Kluck (The Astrophysical Journal)
Starburst wind models predict that metals and energy are primarily carried out of the disk by hot gas ( T > 10 ^6 K), but the low energy resolution of X-ray CCD observations results in large uncertainties on the mass and energy loading. Here, we present evidence for a fast soft X-ray wind from the prototypical starburst galaxy M82 using deep archival observations from the Reflection Grating Spectrometer on XMM-Newton. After characterizing the complex line-spread function for the spatially extended outflow ( $≈ 4^{′} $ ), we perform emission-line fitting to measure the velocity dispersion, σ _v , from O viii (0.65, 0.77 keV), Ne x (1.02 keV), and Mg xii (1.47 keV). For the T ≈ 3 × 10 ^6 K gas, O viii yields a velocity dispersion of ${σ }_{v}={1160}_{-90}^{+100}$ km s ^−1 , implying a wind speed that is significantly above the escape velocity ( v _esc ≲ 450 km s ^−1 ). Ne x ( ${σ }_{v}={550}_{-150}^{+130}$ km s ^−1 ) and Mg xii ( σ _v < 370 km s ^−1 ) show less velocity broadening than O viii , hinting at a lower wind speed or smaller opening angle on the more compact spatial scales traced by the T ≈ (0.6−1) × 10 ^7 K gas. Alternatively, these higher energy emission lines may be dominated by shock-heated gas in the interstellar medium. Future synthesis of these measurements with performance verification observations of the E = 2−12 keV wind in M82 from the Resolve microcalorimeter on the X-ray Imaging and Spectroscopy Mission will inform the phase structure and energy budget of the hot starburst wind.